Unformatted text preview: + 1) 23, since k + 1 > 1. Case 2 ( k + 1 ≥ 8): Now T ( k + 1) = 4 T ( b k +1 2 c ) + 7 by the deﬁnition < 4(7( b k +1 2 c ) 23) + 7 by IH since b k +1 2 c ≤ k +1 2 ≤ k when k ≥ 1 ≤ 4(7( k +1 2 ) 23) + 7 since b k +1 2 c ≤ k +1 2 = 7( k + 1) 212 + 7 < 7( k + 1) 23 which is what we needed to show 1...
View
Full
Document
This note was uploaded on 12/24/2010 for the course CS CS 173 taught by Professor Fleck during the Spring '10 term at University of Illinois, Urbana Champaign.
 Spring '10
 fleck

Click to edit the document details